1
$\begingroup$

$p\land (q\lor \lnot r)\lor(\lnot p \lor \lnot q \lor r)$

how do I solve this? Can I just combine $(q\lor \lnot r)\lor(\lnot p \lor \lnot q \lor r)$?

$\endgroup$
  • 3
    $\begingroup$ The expression is of the form $p\land A\lor B$, which is ambiguous. $\endgroup$ – Arthur Sep 5 '17 at 10:38
  • 1
    $\begingroup$ What do you mean by "solve"? Do you need a truth value? Also as Arthur mentioned, you need to put additional parentheses. Your expression could either be: $ p∧((q∨∼r)∨(∼p∨∼q∨r))$ or $ (p∧(q∨∼r))∨(∼p∨∼q∨r)$ $\endgroup$ – Keen Sep 5 '17 at 11:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.